Rethinking the name; The problem of the name Candrakiraṇa in the oldest Javanese prosody - Aminullah, Zakariya Pamuji (Wacana, Journal of the Humanities of Indonesia, 2021)
The oldest written text in Javanese literature is Candrakiraṇa, one of its parts, the Amaramālā, mentions “Indra” as a king of the Śailendra dynasty. This work is essential because it includes various elements of prosody which the authors of kakawin needed to compose their literary work. For many years, some Javanese scholars had been debating the proper name of this text, using only one manuscript, LOr 4570, a copy of the incomplete gebang manuscript from the PNRI, which does not have a prologue or an epilogue mentioning its precise name. However, reading L 298, a lontar in the Merapi-Merbabu Collection, this manuscript clearly demonstrates that the name of this oldest text is Candrakiraṇa. This begs the question: Is there any relationship between the name and the content itself? This article presents pertinent arguments indicating that the name proposed can be accounted for both factually and conceptually.